Nonproliferation Regime under Modern Circumstances - N. V. Sinitsyna (Московский журнал международного права, 2008)
This article is dedicated to the nuclear nonproliferation problem. The author explains the urgency of the issue, especially in the light of the recent international events. During the last years the Nonproliferation Treaty has been criticized for the world community can not agree how to apply the Nonproliferation Treaty towards the certain states that are suspected of creation of their own nuclear weapon potentials Under circumstances of the “crisis” of the Nonproliferation Treaty it makes sense providing a historical review of the Treaty in order to see what conceptual ideas underlie the nuclear weapon international control, which plans that existed before influenced the essence of the Treaty and which political realties the Treaty reflected initially. Such an analysis will make clear what kind of changes have occurred since the time when the Treaty was signed and which provisions fail to respond with modern circumstances. Subsequently it will help to work out propositions aimed at improving and strengthening of the nonproliferation regime.